Multi-touch, gesture-based simulations: Impacts on learning optical imaging and mental model development. (February 2020) - Hung, Cheng-Yu; Xu, Wei-Wei; Lin, Yu-Ren
Abstract: This study examines the effects of different simulation interface designs on students' conceptual understanding of optical imaging and mental model development, and clarifies these design implications on students' behavioral performance and average residence time. We developed simulations of two different interfaces—gesture- and mouse-based simulations—to collect and compare data from two respective student groups. We utilized a quasi-experimental design, and selected and assigned 64 sixth-grade students to the gesture-and mouse-based simulation groups. The results showed a significant difference between the mental model tests (MMT) of the two groups. Specifically, among the three aspects of a mental model, answer (phenomenon) and explanations (which explain the phenomenon) showed more significant differences with the use of gesture-based than mouse-based simulations. The multivariate analysis of variance results indicated that students using gesture-based simulations demonstrated a longer average residence time than those using mouse-based simulations. Further, the study results suggest that compared to a traditional mouse-based interface, the application of multi-touch gestures in optical imaging concept learning enabled not only the development of a more complete mental model but also the improvement of students' science explanation skills. Highlights: Mouse- and gesture-based simulations significantly enhanced conceptual learning. Complete mental models could be created with multi-touch gesture-based simulations. Multi-touch gesture-based simulation improved students' science explanation skills.